Active galactic nuclei in diverse galactic environments - Patel, Divya; Robertson, Clayton; Holwerda, Benne; Pimbblet, Kevin; Kirkpatrick, Allison; De Propris, Roberto; Liske, Jochen (Cambridge University Press (CUP), 2026)
We examine how the presence of active galactic nuclei (AGN) correlates with location in large-scale cosmic structures using the Galaxy and Mass Assembly (GAMA) survey across the G09, G12, and G15 fields. Our sample contains 18 927, 9 273, and 1 148 galaxies for highly dense filaments, moderately dense tendrils, and highly underdense voids, respectively. AGN are identified among emission-line galaxies using Baldwin-Phillips-Terlevich (BPT) diagnostic diagrams based on [NII], [SII], and [OI]. We compare AGN fractions across filament, tendril, and void regions and as a function of distance from the nearest filament centreline. Our results reveal a mild excess in filaments compared to voids when using [SII]- and [NII]-based classifications, while no significant environmental dependence is found for [OI]-based classifications. Overall, we find a weak environmental trend with AGN activity, which suggests that the local environment does not always dominate AGN activity; instead, secular processes are likely to be at play. Our findings are consistent with previous studies reporting only marginal preferences for overdense environments for AGN.